Effects of process parameters on the quality aspects of weld-bead in laser welding of NiTinol sheets. Issue 6 (26th April 2019) - Datta, Susmita; Raza, Mohammad Shahid; Saha, Partha; Pratihar, D. K
ABSTRACT: The effects of process variables, like scan speed and laser power, on the quality of bead-on-plate welding of NiTinol sheets were investigated. The measured quality aspects for the weld-bead profile were bead geometry, changes in microstructure, variation of microhardness value along the weld-bead, extent of oxide contamination during welding, Ti/Ni ratio after welding, changes in tensile strength of the welded samples and corrosion behavior of the welded and parent materials. The laser weld-bead profile changed from the shape of a stemless wineglass to that with a prominent leg. Dimensional aspects of weld-bead geometry showed a decreasing trend with increasing scan speed. However, an increasing trend of the same was observed with power. The Ti/Ni ratio on the top surface after welding was found to decrease with scan speed at a particular power. Oxide contamination during welding followed the same pattern of variation as that of the Ti/Ni ratio. Microhardness values gradually increased from the weld centerline to the base metal. Formation of brittle intermetallic compounds reduced the tensile strength of the material after welding. A dual failure mode for the welded sample was observed, whereas a single mode of failure was detected for the parent material. The corrosion properties of the welded samples were better than that of the parent material.